Evaluation of sampling strategies for estimating ammonia emission factors for pig fattening facilities. (December 2015) - Ulens, Tim; Daelman, Matthijs R.J.; Mosquera, Julio; Millet, Sam; van Loosdrecht, Mark C.M.; Volcke, Eveline I.P.; Van Langenhove, Herman; Demeyer, Peter
Abstract : Determining ammonia emission factors (EF) for fattening pig facilities is important from both a regulatory and a research point of view. However, measurements to determine an EF can be time consuming and costly. Several reduced sampling strategies were developed in the past to reduce the costs and measuring time, by taking into account parameters that influence NH3 emissions. A methodology to evaluate the precision and accuracy of estimated EFs solely as a function of the sampling frequency and strategy is demonstrated. This evaluation was done by using two long-term, high frequency datasets which both contained measurements during two consecutive pig fattening periods. These datasets were subjected to simulated sampling strategies. Long-term, low-frequency grab sampling proved to be more accurate than short-term monitoring. Repetitive short-term sampling events result in increased precision, but as this entails higher investment in time and money it is imperative to strike the balance between desired precision and available resources. A method to help as set guidelines to decide upon the number of short-term sampling events or the length of a long-term, low-frequency monitoring strategy is presented. Highlights: Strategies for sampling ammonia emission from fattening pig facilities evaluated. Long-term low-frequency sampling is more accurate than short-term sampling. Guidelines for balancing monitoring cost/effort and accuracy can be developed.